2018
DOI: 10.1186/s13756-018-0352-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-based analysis of Carbapenemase-producing Klebsiella pneumoniae isolates from German hospital patients, 2008-2014

Abstract: BackgroundBy using whole genome sequence data we aimed at describing a population snapshot of carbapenemase-producing K. pneumoniae isolated from hospitalized patients in Germany between 2008 and 2014.MethodsWe selected a representative subset of 107 carbapenemase-producing K. pneumoniae clinical isolates possessing the four most prevalent carbapenemase types in Germany (KPC-2, KPC-3, OXA-48, NDM-1). Isolates were processed via illumina NGS. Data were analysed using different SNP-based mapping and de-novo asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 55 publications
(60 reference statements)
3
42
0
1
Order By: Relevance
“…It is interesting to note that in our study, of the two isolates containing bla OXA-162 , one has also harboured bla OXA-1 . Also, similar to the German and Hungarian studies, bla OXA-162 is co-expressed in both isolates with the bla CTX-M-15 [29,38]. In contrast with other reports where bla OXA-162 was found in clinical isolates, in this study we have identified it in WWTP samples (both influent and effluent).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is interesting to note that in our study, of the two isolates containing bla OXA-162 , one has also harboured bla OXA-1 . Also, similar to the German and Hungarian studies, bla OXA-162 is co-expressed in both isolates with the bla CTX-M-15 [29,38]. In contrast with other reports where bla OXA-162 was found in clinical isolates, in this study we have identified it in WWTP samples (both influent and effluent).…”
Section: Discussionsupporting
confidence: 83%
“…The most frequent carbapenemases genes (e.g. bla OXA-48, bla KPC-2, bla NDM-1 and bla OXA-162 ) found in the majority of the influent, effluent and clinical isolates are those reported as prevalent both in Romania and in other geographical areas [29]. Previous studies performed in Romania on carbapenem-non-susceptible Klebsiella pneumoniae clinical isolates have shown that bla OXA-48 was by far the most predominant genotype, followed by bla NDM-1 and bla KPC-2 [30,31,32].…”
Section: Discussionmentioning
confidence: 98%
“…Although bla NDM has been found on bacterial chromosomes (82)(83)(84), the vast majority of carriage occurs on plasmids, which play a vital role in dissemination. bla NDM has been reported to be carried on plasmids with a variety of replicon types (33,82,(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). There are a total of 355 bla NDM -carrying plasmids with complete sequences available in GenBank (accessed on 8 January 2018) (see Data Set S2 in the supplemental material).…”
Section: Plasmids Carrying Bla Ndmmentioning
confidence: 99%
“…To survey global AMR potential, we blasted the contamination-filtered reads against the Comprehensive Antibiotic Resistance Database (CARD) 45 and assigned the top match for each read to its respective gene family under the Antibiotic Resistance Ontology (ARO). To identify AMR genes encoded by A. baumannii and K. pneumoniae, which were both present in our studied host species ( Figure S7), we extracted reads that mapped to these bacterial genomes with bwa 46,47 . We confirmed that reads from both bacterial species exhibited characteristic deamination patterns consistent with historical DNA damage ( Figure 5B-C) and subsequently processed these reads in CARD, as above.…”
Section: Antimicrobial Resistance Genes Are Present In Wild Animal MImentioning
confidence: 99%
“…The Illumina sequencing control phage PhiX was spiked into our sequencing runs and has previously been reported to have been erroneously integrated into many microbial genomes 23,67 . Reads were therefore mapped to PhiX (accession: GCA_000819615.1) with bwa mem v0.7.17 46,47 and the unmapped reads retained with SAMTools v1.9 68 and BEDTools v2.21.0 69 . To remove reads originating from the host organism and human contamination, we mapped all reads in a sample to a combined reference consisting of the human genome 70 (RefSeq accession: GCF_000001405.38) and the respective host genome (GCF_000151905.2 (Gorilla gorilla gorilla) 71 , GCF_003584765.1 (U. arctos horribilis) 72 and GCA_004026565.1 (Rangifer tarandus)) with bwa mem.…”
Section: Data Processingmentioning
confidence: 99%